Estimation of expediency of taking into account the suppleness of outrigger metallic structures nodes in calculation of high-rise building structures - I. V. Astakhov; D. V. Kaliuzhny (Vestnik MGSU)
Introduction. When designing metal structures, many factors are taken into account, including the suppleness of joints, which affects the results of stress-strain calculations of structural elements. In the design of high-rise buildings, outriggers are provided to distribute wind loads between the core and perimeter columns, reducing horizontal displacements. Considering the suppleness in the joints of the outrigger affects the distribution of forces in the building structure elements, as well as on the building deformations. This paper presents an analysis of the influence of considering the suppleness of outrigger joints on the stress-strain state of structural elements of a steel high-rise building.Materials and methods. The research focuses on a structural model of a 60-story building with an outrigger, modelled using the ETABS software. The suppleness of the joints of the outrigger structures was determined using the IDEA StatiCa software.Results. According to the results of static calculations considering the suppleness of the outrigger joints, when placing one outrigger on the 54th floor, the maximum horizontal displacement at the top of the building increased by 2.9 % compared to calculations without considering suppleness. Placing two outriggers increased it by 4.7 %. The maximum axial force value in the outrigger brace decreased by 23 % compared to calculations without considering suppleness, while the maximum bending moment increased by 10 %.Conclusions. When calculating a high-rise building taking into account suppleness, the values of horizontal displacement at the building’s top increase within 5 %. If it is necessary to limit horizontal displacements, calculations should consider the suppleness of the joints in steel outrigger structures. Additionally, considering suppleness in calculations allows reducing the material intensity of the designed outrigger braces, as the determining force is the axial force, which decreases by about 25 % when calculated considering suppleness.